Electromagnetic shielding material with ultralow percolation threshold and preparation method and application thereof
By constructing a selective dispersed structure and a microscopic isolation structure in the PLA system, the phase interface between polyurethane-coated carbon nanotubes and thermoplastic polyurethane elastomers is used to form a conductive network, which solves the problem of uneven dispersion caused by high content of conductive fillers in the PLA conductive system, and realizes an ultra-low permeability threshold electromagnetic shielding material and improved mechanical properties.
Patent Information
- Application Number
- CN202510075283.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-17
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-01-17
AI Technical Summary
The high content of conductive fillers in the existing PLA conductive system leads to uneven dispersion, affecting electromagnetic shielding performance, and reducing the mechanical properties and processing properties of PLA.
By constructing a selective dispersed structure of conductive fillers in the PLA system or introducing microscopic isolation structures, a conductive network is formed using the phase interface between polyurethane-coated carbon nanotubes and thermoplastic polyurethane elastomers to form a conductive network, reducing the amount of conductive fillers and improving dispersion.
The electromagnetic shielding material with ultra-low permeability threshold is achieved, which significantly improves the electromagnetic shielding performance of the material and improves the mechanical strength and processing performance of PLA.
Smart Images

Figure CN119875332A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of polymer processing and electromagnetic shielding, and in particular relates to an electromagnetic shielding material with an ultra-low percolation threshold, a preparation method thereof and an application thereof. Background Art
[0002] With the rapid development of the global economy, the shortage of oil resources and environmental pollution have become increasingly prominent. The development of environmentally friendly materials has become an important research direction in the field of materials. Polylactic acid (PLA), as a bio-based, biodegradable polymer material, has attracted widespread attention because its raw materials are derived from plant resources such as corn, and it has the advantages of being renewable and having sufficient sources. The application areas of PLA cover packaging, fiber, 3D printing materials, biomedicine and many other aspects, showing great development potential.
[0003] However, in practical applications, there are still many challenges in the research of PLA conductive systems. In traditional methods, in order to achieve good conductive properties, it is often necessary to add a high content of conductive fillers, such as carbon nanotubes, graphene or metal nanoparticles, to the PLA matrix. However, a high content of conductive fillers can easily lead to uneven dispersion in the PLA system, thus affecting the overall performance of the material, especially the electromagnetic shielding performance is difficult to reach the ideal level. In addition, high filler content may also reduce the mechanical properties and processing properties of PLA, limiting its practical application range. In this context, the researchers proposed a strategy of constructing a selective dispersion structure of conductive fillers in the PLA system or introducing a micro-isolation structure, which can not only significantly reduce the amount of conductive fillers, but also effectively improve their dispersibility, thereby improving the electromagnetic shielding performance of the material. This method provides a new research direction for the development of high-performance, low-cost, and environmentally friendly PLA electromagnetic shielding materials.
[0004] In addition, PLA and most elastomers have significant differences in chemical structure, which usually manifests as incompatibility. This incompatibility prevents the two from forming a uniform phase structure when mixed, but instead repel each other to form a two-phase separation system. In this system, the PLA phase and the elastomer phase exist independently, and this separation characteristic provides convenient conditions for constructing selectively dispersed structures or isolated structures. For example, conductive fillers can be preferentially distributed in a certain phase or form a conductive network at the interface between the two phases, thereby further reducing the amount of filler and optimizing its dispersibility and functional performance. The proposal of this strategy not only provides theoretical support for improving the electromagnetic shielding performance of PLA-based composites, but also opens up new ideas for material structure design. Summary of the invention
[0005] The technical purpose of the present invention is to provide an electromagnetic shielding material with an ultra-low percolation threshold and a preparation method and application thereof, which not only has an ultra-low percolation threshold but also has excellent electromagnetic shielding effectiveness.
[0006] The present invention provides an electromagnetic shielding material with an ultra-low percolation threshold. The electromagnetic shielding material is formulated in the following proportions by mass: 50-70 parts of polylactic acid, 30-70 parts of thermoplastic polyurethane elastomer, 0.05-3 parts of chain extender, 0.5-10 parts of modified filler, and 0.5-3 parts of antioxidant; wherein the modified filler is a polyurethane-coated carbon nanotube with a diameter of 2-20 nm.
[0007] Compared with the prior art, the carbon nanotube surface coating of the present invention is polyurethane, and the polarity of polyurethane and thermoplastic polyurethane elastomer (TPU) is similar, so as the melt blending time is extended, the carbon nanotube (CNS) located in the polylactic acid matrix will gradually migrate to the phase interface between polylactic acid and thermoplastic polyurethane elastomer, and then migrate into the thermoplastic polyurethane elastomer. When the carbon nanotube is at the phase interface between polylactic acid and thermoplastic polyurethane elastomer, it will form a microscopic isolation structure and form a large number of conductive networks, thereby greatly reducing the content of carbon nanotubes in the polymer matrix that constitutes the conductive network. The polyurethane-coated carbon nanotube can not only increase the interfacial interaction force between polylactic acid and thermoplastic polyurethane elastomer copolymer, but also increase the viscosity of the matrix. In addition, the carbon nanotube can also serve as an efficient nucleating agent for the polylactic acid matrix, significantly increasing the crystallization rate of the matrix and improving the mechanical strength of the matrix.
[0008] In some other embodiments, the melt index of the polylactic acid is 3-10 g / 10 min, and the polylactic acid is L-polylactic acid or D-polylactic acid.
[0009] In some other embodiments, the structure of the thermoplastic polyurethane elastomer is obtained by alternating hard segments and soft segments, wherein the soft segments are composed of flexible long chains of polyols, and the hard segments are composed of diisocyanates and chain extenders.
[0010] In some other embodiments, the chain extender is selected from one or more of a compound containing multiple epoxy groups, a compound containing multiple isocyanate groups, and anhydride compounds.
[0011] In some other embodiments, the antioxidant is selected from one or more of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, tris(2,4-di-tert-butylphenyl) phosphite, triphenyl phosphite, and 4,4'-bis(α,α-dimethylbenzyl)diphenylamine.
[0012] In some other embodiments, the electromagnetic shielding material has an electromagnetic shielding performance of not less than 20 dB in the X-band with a frequency range of 8.2-12.4 GHz.
[0013] In some other embodiments, in the electromagnetic shielding material, the modified filler is in the following state: uniformly dispersed in one phase and / or dispersed at the interface between two phases.
[0014] The second object of the present invention is to provide a method for preparing an electromagnetic shielding material, the preparation method specifically comprising the following steps: Polylactic acid, thermoplastic polyurethane elastomer, antioxidant, chain extender and modified filler are mixed evenly according to weight ratio, and then melt-extruded to obtain an electromagnetic shielding material with an ultra-low percolation threshold.
[0015] The third object of the present invention is to provide a method for preparing an electromagnetic shielding material, the preparation method specifically comprising the following steps: Polylactic acid, antioxidant, chain extender and modified filler are mixed evenly according to a weight ratio, then melt-blended, thermoplastic polyurethane elastomer is added according to a weight ratio, and then melt-blended to obtain an electromagnetic shielding material with an ultra-low percolation threshold.
[0016] Furthermore, the preparation method specifically comprises the following steps: Lactic acid, antioxidant, chain extender and modified filler are mixed evenly according to the weight ratio, added into an internal mixer for melt blending for 5-15 minutes, thermoplastic polyurethane elastomer is added according to the weight ratio, and melt blending is performed again for 1-15 minutes to obtain an electromagnetic shielding material with an ultra-low percolation threshold, wherein the melt extrusion temperature is 20-40°C above the melting point of polylactic acid, and the screw speed is 30-80 rpm.
[0017] Compared with the prior art, the electromagnetic shielding material with ultra-low percolation threshold and its preparation method provided by the present invention are to first melt-blend polylactic acid and polyurethane-coated carbon nanotubes to prepare a masterbatch. During the melt blending process, the carbon nanotubes are uniformly dispersed in the polylactic acid matrix, and the masterbatch is crushed and dried. The dried masterbatch is melt-blended with a thermoplastic polyurethane elastomer. Due to the large difference in structure and polarity between polylactic acid and thermoplastic polyurethane elastomer, the physical bonding effect is not ideal, resulting in the two phases forming a "bicontinuous structure" or "island structure". However, the surface coating of the carbon nanotubes is polyurethane and the polarity of the thermoplastic polyurethane elastomer is similar, so as to extend the melt blending time, the carbon nanotubes located in the polylactic acid matrix will gradually migrate to the interface between the polylactic acid and the polyurethane elastomer, and then migrate into the polyurethane elastomer. When the carbon nanotubes are at the interface between the polylactic acid and the polyurethane elastomer, a microscopic isolation structure is formed, forming a large number of conductive networks. Thereby greatly reducing the content of the carbon nanotubes in the polymer matrix that constitutes the conductive network. The carbon nanotubes can not only increase the interfacial interaction between polylactic acid and polyurethane elastomer copolymer, but also increase the viscosity of the matrix. In addition, the carbon nanotubes can also serve as an efficient nucleating agent for the polylactic acid matrix, significantly increasing the crystallization rate of the matrix and improving the mechanical strength of the matrix.
[0018] A fourth object of the present invention is to provide an application of an electromagnetic shielding material in the field of electronic equipment, automobile industry or electronic system.
[0019] Compared with the prior art, the present invention has the following advantages: 1. The present invention provides a preparation method, which comprises firstly melt-blending polylactic acid and carbon nanotubes to prepare a masterbatch, and then melt-blending the masterbatch with an elastomer, and controlling the processing time of the second stage to place the carbon nanotubes in different positions, so that different electrical conductivities can be achieved with the same content of carbon nanotubes, thereby preparing an electromagnetic shielding material with an ultra-low percolation threshold; 2. The conductive filler in the material is concentrated and dispersed at the interface between polylactic acid and thermoplastic polyurethane elastomer, and only a small amount of carbon nanotubes is needed to form a continuous conductive network, which solves the problem of easy detachment and poor adhesion of the conductive filler in the mechanical coating-hot pressing molding method, and significantly improves the electromagnetic shielding performance through the dispersion of the conductive filler in the material. The material has good application prospects in the fields of electronic communications;
[0020] 3. The present invention plays a triple role as a conductive filler: first, it is located at the interface between polylactic acid and thermoplastic polyurethane elastomer to improve the interfacial force; second, it improves the viscosity of the matrix; third, as a nucleating agent, it significantly improves the crystallinity of the PLA matrix, thereby improving the mechanical strength of the matrix; 4. The preparation method provided by the present invention is simple, efficient and easy to realize industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 The volume conductivity results of PLA / TPU / CNS systems with different CNS contents are shown in the figure; Figure 2 The electromagnetic shielding performance results of PLA / TPU / CNS system with different CNS contents in X-band; Figure 3 The electromagnetic shielding performance results of PLA / TPU / CNS-1wt% (Examples 1-4) systems with different processing times are shown in FIG. Figure 4 TEM analysis diagram of samples of Examples 1-4. DETAILED DESCRIPTION
[0022] In order to make the above-mentioned purposes, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below. It should be noted that the following embodiments are only used to illustrate the implementation method and typical parameters of the present invention, and are not used to limit the parameter range described in the present invention. Reasonable changes derived therefrom are still within the scope of protection of the claims of the present invention.
[0023] It should be noted that the endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, and these numerical ranges should be regarded as specifically disclosed in this article.
[0024] Unless otherwise defined, all terms, symbols and other scientific terms used herein are intended to have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. In some cases, terms with conventionally understood meanings are defined herein for the purpose of clarification or ease of reference, and such definitions herein should not be construed as indicating significant differences from conventional understandings in the art. The technical methods described or cited herein are generally well understood by those skilled in the art and are adopted by conventional methods. Unless otherwise stated, the use of commercially available kits, reagents and instruments is carried out in accordance with the protocols and parameters given by the manufacturer.
[0025] The technical effects of the present invention are described below in conjunction with specific embodiments.
[0026] Example 1 The present embodiment provides an electromagnetic shielding material with an ultra-low percolation threshold, which is prepared by the following preparation method: 50 parts of polylactic acid (4032D) and 2 parts of polyurethane-coated carbon nanotubes, 1 part of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, 1 part of tris(2,4-di-tert-butylphenyl) phosphite, and 2 parts of 1,6-hexanediol are added into an internal mixer for melt blending for 8 minutes (blending temperature is 190°C, screw speed is 50 rpm); the blended sample is crushed and dried and melt blended with 50 parts of thermoplastic polyurethane elastomer for 2 min (blending temperature is 190°C, screw speed is 50 rpm), so as to obtain an electromagnetic shielding material with an ultra-low percolation threshold.
[0027] Example 2 The present embodiment provides an electromagnetic shielding material with an ultra-low percolation threshold, which is prepared by the following preparation method: 50 parts of polylactic acid (4032D) and 2 parts of polyurethane-coated carbon nanotubes, 1 part of tris(2,4-di-tert-butylphenyl) phosphite, 1 part of 4,4'-bis(α,α-dimethylbenzyl)diphenylamine, and 2 parts of diethylaminoethanol (DEAE) are added into an internal mixer for melt blending for 8 minutes (blending temperature is 190°C, screw speed is 50 rpm); the blended sample is crushed and dried and melt blended with 50 parts of thermoplastic polyurethane elastomer for 4 min (blending temperature is 190°C, screw speed is 50 rpm), so as to obtain an electromagnetic shielding material with an ultra-low percolation threshold.
[0028] Example 3 The present embodiment provides an electromagnetic shielding material with an ultra-low percolation threshold, which is prepared by the following preparation method: 50 parts of polylactic acid (4032D) and 2 parts of polyurethane-coated carbon nanotubes, 1 part of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], 1 part of triphenyl phosphite, and 1 part of trimethylolpropane are added into an internal mixer for melt blending for 8 minutes (blending temperature is 190°C, screw speed is 50 rpm); the blended sample is crushed and dried and melt blended with 50 parts of thermoplastic polyurethane elastomer for 6 min (blending temperature is 190°C, screw speed is 50 rpm), so as to obtain an electromagnetic shielding material with an ultra-low percolation threshold.
[0029] Example 4 The present embodiment provides an electromagnetic shielding material with an ultra-low percolation threshold, which is prepared by the following preparation method: 50 parts of polylactic acid (4032D) and 2 parts of polyurethane-coated carbon nanotubes, 2 parts of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, 2 parts of tris(2,4-di-tert-butylphenyl) phosphite, 1 part of N,N-dihydroxy(diisopropyl)aniline (HPA), and 1 part of neopentyl glycol (NPG) are added into an internal mixer for melt blending for 8 minutes (blending temperature is 190°C, screw speed is 50 rpm); the blended sample is crushed and dried and melt blended with 50 parts of thermoplastic polyurethane elastomer for 8 min (blending temperature is 190°C, screw speed is 50 rpm), to obtain an electromagnetic shielding material with an ultra-low percolation threshold.
[0030] Example 5 The present embodiment provides an electromagnetic shielding material with an ultra-low percolation threshold, which is prepared by the following preparation method: 50 parts of polylactic acid (4032D), 2 parts of polyurethane-coated carbon nanotubes and 50 parts of thermoplastic polyurethane elastomer, 2 parts of tris(2,4-di-tert-butylphenyl) phosphite, and 2 parts of N,N-dihydroxy(diisopropyl)aniline (HPA) are added into an internal mixer for melt blending for 8 minutes (blending temperature is 190°C, screw speed is 50 rpm), and an electromagnetic shielding material with an ultra-low percolation threshold can be obtained.
[0031] Comparative Example 1 This comparative example provides an electromagnetic shielding material, which is prepared by the following preparation method: 70 parts of polylactic acid (4032D), 2 parts of polyurethane-coated carbon nanotubes and 30 parts of polymethyl methacrylate, 1 part of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, 1 part of 4,4'-bis(α,α-dimethylbenzyl)diphenylamine, 1 part of 1,6-hexanediol, and 1 part of sorbitol are added into a twin-screw extruder for continuous extrusion, and melt-blended in its flow channel for 8 minutes (the temperature of the first blending zone is 170°C, the temperature of the second blending zone is 200°C, the temperature of the third blending zone is 200°C, and the screw speed is 30 rpm).
[0032] Comparative Example 2 The comparative example provides an electromagnetic shielding material, which is prepared by the following preparation method: 50 parts of polylactic acid (4032D), 2 parts of multi-walled carbon nanotubes and 50 parts of polyether block polyamide elastomer, 1 part of tris(2,4-di-tert-butylphenyl) phosphite, 0.5 part of triphenyl phosphite, 0.5 part of 4,4'-bis(α,α-dimethylbenzyl)diphenylamine, 0.5 part of diethylene glycol (DEG), and 0.5 part of triethylene glycol are added into an internal mixer for melt blending for 8 minutes (blending temperature is 200°C, screw speed is 50 rpm), and an electromagnetic shielding material with an ultra-low percolation threshold can be obtained.
[0033] Comparative Example 3 This comparative example provides an electromagnetic shielding material, which is prepared by the following preparation method: 50 parts of polylactic acid (4032D), 2 parts of polyurethane-coated carbon nanotubes and 50 parts of polyether block polyamide elastomer, 2 parts of 4,4'-bis(α,α-dimethylbenzyl)diphenylamine, and 2 parts of N,N-dihydroxy(diisopropyl)aniline (HPA) are added into an internal mixer for melt blending for 8 minutes (blending temperature is 200°C, screw speed is 50 rpm); an electromagnetic shielding material with an ultra-low percolation threshold can be obtained.
[0034] In order to investigate the electrical properties of the composite material prepared by the method of the present invention, the volume conductivity and electromagnetic shielding of the samples obtained in Examples 1-5 and Comparative Examples 1-3 were tested. The results are as follows: Figure 1-Figure 4 As shown, among them. Figure 1 The volume conductivity results of PLA / TPU / CNS systems with different CNS contents are shown in Figure 2. Figure 1 It can be seen that through linear fitting, its percolation threshold shows an ultra-low level of only 0.03 wt%. Figure 2 The electromagnetic shielding performance results of PLA / TPU / CNS system with different CNS contents in X-band are shown in Figure 2. Figure 2 It can be seen that through linear fitting, its percolation threshold shows an ultra-low level of only 0.03 wt%; Figure 3 The electromagnetic shielding performance results of PLA / TPU / CNS-1wt% (Examples 1-4) systems with different processing times are shown in FIG. Figure 4 TEM analysis diagram of samples of Examples 1-4. Figure 4 It can be seen that the atomic contrast of PLA and TPU is different, so PLA presents a "bright" area compared with TPU, while TPU presents a "dark" area, and it can be seen that with the extension of processing time, there is direct evidence that CNS migrates from the PLA phase to the TPU phase.
[0035] Although the disclosure is disclosed as above, the protection scope of the disclosure is not limited thereto. Those skilled in the art can make various changes and modifications without departing from the spirit and scope of the disclosure, and these changes and modifications will fall within the protection scope of the present invention.
Claims
1. An electromagnetic shielding material with an ultra-low percolation threshold, characterized in that: The electromagnetic shielding material is formulated in the following proportions by mass: polylactic acid: 50-70 parts, thermoplastic polyurethane elastomer: 30-70 parts, chain extender: 0.05-3 parts, modified filler: 0.5-10 parts, antioxidant: 0.5-3 parts; wherein the modified filler is a polyurethane-coated carbon nanotube with a diameter of 2-20 nm.
2. The electromagnetic shielding material according to claim 1, characterized in that: The melt index of the polylactic acid is 3-10 g / 10 min, and the polylactic acid is left-handed polylactic acid or right-handed polylactic acid.
3. The electromagnetic shielding material according to claim 1, characterized in that The structure of the thermoplastic polyurethane elastomer is obtained by alternating hard segments and soft segments, wherein the soft segments are composed of flexible long chains of polyols, and the hard segments are composed of diisocyanate and a chain extender.
4. The electromagnetic shielding material according to claim 1, characterized in that The chain extender is selected from one or more of a compound containing multiple epoxy groups, a compound containing multiple isocyanate groups, and anhydride compounds; And / or, the antioxidant is selected from one or more of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, tris(2,4-di-tert-butylphenyl) phosphite, triphenyl phosphite, and 4,4'-bis(α,α-dimethylbenzyl)diphenylamine.
5. The electromagnetic shielding material according to claim 1, characterized in that: The electromagnetic shielding material has an electromagnetic shielding performance of not less than 20 dB in the X-band with a frequency range of 8.2-12.4 GHz.
6. The electromagnetic shielding material according to claim 1, characterized in that: In the electromagnetic shielding material, the modified filler is in the following state: uniformly dispersed in one phase and / or dispersed at the interface between two phases.
7. A method for preparing an electromagnetic shielding material according to any one of claims 1 to 6, characterized in that: The preparation method specifically comprises the following steps: Polylactic acid, thermoplastic polyurethane elastomer, antioxidant, chain extender and modified filler are mixed evenly according to weight ratio, and then melt-extruded to obtain an electromagnetic shielding material with an ultra-low percolation threshold.
8. A method for preparing an electromagnetic shielding material according to any one of claims 1 to 6, characterized in that: The preparation method specifically comprises the following steps: Polylactic acid, antioxidant, chain extender and modified filler are mixed evenly according to a weight ratio, then melt-blended, thermoplastic polyurethane elastomer is added according to a weight ratio, and then melt-blended to obtain an electromagnetic shielding material with an ultra-low percolation threshold.
9. The preparation method according to claim 8, characterized in that: The preparation method specifically comprises the following steps: Lactic acid, antioxidant, chain extender and modified filler are mixed evenly according to the weight ratio, added into an internal mixer for melt blending for 5-15 minutes, thermoplastic polyurethane elastomer is added according to the weight ratio, and melt blending is performed again for 1-15 minutes to obtain an electromagnetic shielding material with an ultra-low percolation threshold, wherein the melt extrusion temperature is 20-40°C above the melting point of polylactic acid, and the screw speed is 30-80 rpm.
10. Use of the electromagnetic shielding material according to any one of claims 1 to 6 in the field of electronic equipment, automobile industry or electronic system.
Citation Information
Patent Citations
Dispersions for additive manufacturing comprising discrete carbon nanotubes
CA3213250A1
Electromagnetic shielding polymer foamed material and preparation method thereof
CN107603004A
Electromagnetic shielding composite material with asymmetric structure, preparation method thereof and electromagnetic shielding device
CN114957786A
3D printing wave structure shape memory composite material with controllable low-frequency electromagnetic shielding performance and preparation method thereof
CN115558267A
Lightweight high-electromagnetic-shielding composite foam material as well as preparation method and application thereof
CN118271811A
Cited By
Broadband electromagnetic shielding pearl wool material and preparation method thereof
CN122302396A